The Value of Geological Human Capital in the Improvement and Maximisation of Ore Deposit Value – The Kalgoorlie Consolidated Gold Mines Experience - D Cooke (The Australasian Institute of Mining and Metallurgy, 2011)
In 2010, Kalgoorlie Consolidated Gold Mines (KCGM) was Australia’s largest gold producer, with total annual production of 788 000 ounces. Of the gold produced by KCGM in 2010, 95 per cent was extracted from the Fimiston open pit, also known as the Superpit. The Fimiston operation encompasses the historic Golden Mile, from which more than 55 million ounces of gold have been extracted from the world-class Fimiston lode style mineralisation.The operational performance of the KCGM Fimiston open pit was reviewed for the period between 2005 and 2010. Key performance metrics reviewed included mined tonnes and grade, cost per ounce of gold produced and the mine to mill reconciliation trends. The years 2007 and 2008 were characterised by a decline in performance against key performance metrics. The ore zones were diluted, with the excess tonnes mined resulting in lower grade and an increase in the cost per ounce. Poor reconciliation between ore mined, the ore reserve model and the grade control polygons was also observed.A series of improvement initiatives were implemented in late 2008. As a result of changes made to the grade control and mining practices, the site performance recovered. Unplanned dilution was reduced, which had a positive impact on mined grade. The lower tonnes combined with higher grade reduced the cost per ounce to below budgeted levels in 2009 and 2010, enhancing the profitability of the operation. The operational performance between 2005 and 2010 was compared to the turnover statistics for the KCGM geology department over the same period. Turnover accelerated between 2005 and 2007, peaking at an annualised rate of 43 per cent. With the onset of the Global Financial Crisis and the implementation of retention initiatives, turnover reduced significantly between 2008 and 2010. A strong consistent correlation was observed between the turnover trends in geology and the performance of the grade control function and resultant site metrics.The cost of turnover is known intuitively, however, rarely quantified. To evaluate the benefit of the improved performance, a detailed financial model was used to quantify the impact of the grade control function. In 2010, the headgrade exceeding budget by just four per cent contributed an additional A$24 M of value to KCGM. In contrast, if the 2008 performance had been replicated in 2010 (-9 per cent on headgrade), the result would have removed A$61 M in value from the business. The KCGM experience between 2005 and 2010 demonstrates the value of human capital in a mining operation and the importance of a high performing geology grade control team to the profitability of a mining operation.